Cheramus iranicus, a new species of ghost shrimp (Decapoda: Axiidea: Callianassidae) from the Persian Gulf, Iran - Sepahvand, Vahid; Momtazi, Farzaneh; Tudge, Christopher (Zootaxa, 2015)
A new species of callianassid ghost shrimp is described from the Persian Gulf, Iran. Cheramus iranicus sp. nov. is the first member of Cheramus described from Iranian subtidal waters and can be differentiated by a large cheliped with a ventroproximal spine on the merus and 7 spines on the ventral margin of the ischium, the endopod of the uropod has 4 movable spines on the distal margin and the posterior margin of the telson is strongly bilobed with a prominent medial tooth and two pairs of lateral movable spines. It is compared to other described Cheramus-like species showing a high degree of morphological similarity.